Fertility Preservation in Gynecological Cancers - Shakuntala Chhabra; Imran Kutchi (SAGE Publishing, 2013)
For cancers of reproductive system in women, fertility preservation is complex. Fertility is also affected by therapies, however prevention is possible. Radiotherapy affects gonads, uterus, and subsequent pregnancy outcomes in all ages. However, degree and damage depend on dose, irradiation field, and age at the time of exposure. Ovarian transposition is considered if ovarian involvement is unlikely. Gonadotoxic effects of chemotherapy are related to agent's type, cumulative doses, age, and ovarian reserve. Some agents are highly toxic. Rendering follicular development quiescent by suppression of gonadotropins does reduce the ovarian damage. Simple or radical trachelectomy can be used in early cervical cancer. Fertility saving surgery is possible only in early stage low grade epithelial cancers of the ovary, however, in germ cell tumors even in advanced stages it may be possible to preserve fertility. There are no standard recommendations for endometrial cancer. Embryo, oocyte, and ovarian tissue cryopreservation are possible. The human embryo is very resistant to damage. In view of these possibilities, it is advocated that attention to long term health and quality of life in gonadotoxic therapy must be incorporated into plans as early as possible.